2011
DOI: 10.1105/tpc.111.089581
|View full text |Cite|
|
Sign up to set email alerts
|

The Arabidopsis Na+/H+ Antiporters NHX1 and NHX2 Control Vacuolar pH and K+ Homeostasis to Regulate Growth, Flower Development, and Reproduction  

Abstract: Intracellular Na + /H + (NHX) antiporters have important roles in cellular pH and Na + , K + homeostasis. The six Arabidopsis thaliana intracellular NHX members are divided into two groups, endosomal (NHX5 and NHX6) and vacuolar (NHX1 to NHX4). Of the vacuolar members, NHX1 has been characterized functionally, but the remaining members have largely unknown roles. Using reverse genetics, we show that, unlike the single knockouts nhx1 or nhx2, the double knockout nhx1 nhx2 had significantly reduced growth, small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
380
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(400 citation statements)
references
References 63 publications
(100 reference statements)
20
380
0
Order By: Relevance
“…These phenotypes are probably independent of mis-regulation of V-ATPase because vha-a2 vha-a3 did not show obvious phenotypes in response to external K + perturbations [34]. K + translocation into the lumen can be mediated by vacuolar NHX-type K + /H + antiporters such as NHX1 [51][52][53]. Relevant to this finding, the activity of NHX1 is shown to be regulated by another calcium sensor, calmodulin [54].…”
Section: Discussionmentioning
confidence: 81%
“…These phenotypes are probably independent of mis-regulation of V-ATPase because vha-a2 vha-a3 did not show obvious phenotypes in response to external K + perturbations [34]. K + translocation into the lumen can be mediated by vacuolar NHX-type K + /H + antiporters such as NHX1 [51][52][53]. Relevant to this finding, the activity of NHX1 is shown to be regulated by another calcium sensor, calmodulin [54].…”
Section: Discussionmentioning
confidence: 81%
“…AtNHX1 and AtNHX2 are highly expressed in many tissues, while AtNHX3 and AtNHX4 are exclusively expressed in flowers and roots (Aharon et al, 2003, Yokoi et al, 2002. Recent results also suggested that NHX1 and NHX2 are vacuolar K + /H + exchangers that control vacuolar pH and K+ homeostasis, they are essential for active K + uptake at the tonoplast, osmotic adjustment and turgor regulation, and that they play a unique role in stomatal function (Bassil et al, 2011, Barragan et al, 2012.…”
Section: Introductionmentioning
confidence: 99%
“…In the phylogenetic tree, AtNHX5 and 6 constituted a separate phylogenetic branch different from that formed by AtNHX1 to 4 (Yokoi et al, 2002;Aharon et al, 2003). Furthermore, AtNHX5 and 6 localize in the Golgi and trans-Golgi network (Bassil et al, 2011a), whereas AtNHX1 to 4 localize in the vacuole and tonoplast (Yokoi et al, 2002;Bassil et al, 2011b;Barragán et al, 2012). These data suggest existence of possibly different mechanisms by which AtNHX1 and 5 maintain the intracellular ion homeostasis and enhance the plant salt stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Among these eight NHXs, AtNHX1 is the most widely studied NHX; the roles of other NHXs remain largely unknown. Studies have revealed that AtNHX1 and 2 localize in the vacuole and tonoplast and have an important role in maintaining the intracellular pH and K + homeostasis (Yokoi et al, 2002;Bassil et al, 2011b;Barragán et al, 2012). Furthermore, atnhx1 and atnhx2 double knockout mutants displayed high sensitivity to salt stress, whereas overexpression of these genes increased the salt tolerance of the plants (Apse et al, 1999;Yokoi et al, 2002;Bassil et al, 2011b;Barragán et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation